Schedule of Classes, Summer 2009 - University of Wisconsin-Milwaukee. Department of Enrollment Services (University of Wisconsin-Milwaukee, 2009)
PDF version of the UW-Milwaukee Schedule of Courses for the Fall 2008 term. Includes registration policies and lists of available classes during this term.
Keywords: Academics; Department of Enrollment Services; Curriculum